Selective esterification of glycerol over ionic liquid functionalized cellulose (IMD-Si/HSO4@Cellulose) under energy-efficient microwave irradiation. Issue 9 (6th April 2022) - Khan, Nida; Khan, Mohd Umar; Siddiqui, Zeba N.
Abstract : A green and sustainable route for selective esterification of glycerol has been developed. The high selectivity of tri-acetin (99%), recyclability of catalyst and overall green methodology were the advantageous features. Abstract : A green and sustainable route for selective esterification of glycerol has been developed. Selectivity towards triacetin was investigated in the esterification of glycerol using highly efficient silica-based imidazolium hydrogen sulphate supported on cellulose (IMD-Si/HSO4 @Cellulose) as a heterogeneous catalyst. The cellulose-supported acidic ionic liquid material, IMD-Si/HSO4 @Cellulose, was synthesized with cellulose in acetone by simple stirring of the ionic liquid (IMD-Si/HSO4 ). The synthesized catalyst was characterized by various techniques such as scanning electron microscopy/energy dispersive X-ray (SEM/EDX), elemental mapping, powder X-ray diffraction (XRD), transmission electron microscopy (TEM), thermogravimetric analysis (TGA), and Fourier transform infrared (FTIR) spectroscopy analyses. IMD-Si/HSO4 @Cellulose showed excellent activity (100% conversion) and greater selectivity (99%) for the esterification of glycerol leading to the formation of triacetin under microwave irradiation in the minimum time (8 min). The catalyst was reused in up to five runs with insignificant loss in catalytic activity.